2005
DOI: 10.1021/es048766c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Superoxide as an Electron Shuttle for Iron Acquisition by the Marine Cyanobacterium Lyngbya majuscula

Abstract: Reduction of iron from the ferric state to the ferrous state is one strategy employed by microorganisms in nearneutral environments to increase its biological availability. In recent years, the existence of mobile reducing agents produced bymicroorganismsto promote iron reduction, known as electron shuttles, has been demonstrated. Production of electron shuttles has been shown for several organisms, employing a variety of mostly organic molecules as the electron carrier. Here we show that the coastal cyanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 44 publications
8
153
2
1
Order By: Relevance
“…The other major ROS sources in photosynthetic organisms are certain enzymatic systems (Halliwell and Gutteridge, 1999), and results of Western blotting using antibody raised against the human neutrophil cytochrome b558 large subunit (gp91phox, a sub-unit of NADPH oxidase) showed that C. marina generates ROS possibly through a plasma membrane NADPH-dependent enzymatic pathway (Kim et al, 2000). Our experiments showed that ROS production was significantly enhanced upon addition of vitamin K 3 , while ROS production was inhibited by dicumarol ( Rose et al (2005) proposed that the marine cyanobacterium Lyngbya majuscula may use superoxide as an electron shuttle to reduce Fe(III) for iron uptake.…”
Section: Nutrients and Ros Productionmentioning
confidence: 74%
“…The other major ROS sources in photosynthetic organisms are certain enzymatic systems (Halliwell and Gutteridge, 1999), and results of Western blotting using antibody raised against the human neutrophil cytochrome b558 large subunit (gp91phox, a sub-unit of NADPH oxidase) showed that C. marina generates ROS possibly through a plasma membrane NADPH-dependent enzymatic pathway (Kim et al, 2000). Our experiments showed that ROS production was significantly enhanced upon addition of vitamin K 3 , while ROS production was inhibited by dicumarol ( Rose et al (2005) proposed that the marine cyanobacterium Lyngbya majuscula may use superoxide as an electron shuttle to reduce Fe(III) for iron uptake.…”
Section: Nutrients and Ros Productionmentioning
confidence: 74%
“…Indeed, oxidation of Mn(II) to Mn oxides by a common marine bacterium, Roseobacter AzwK-3b, was found to be a consequence of enzymatic extracellular production of O 2 − , which served as the terminal oxidant of Mn(II) (19). Although extracellular superoxide production has been documented in pathogenic bacteria (20) and phytoplankton (21), very little is known about the occurrence of this process in nonpathogenic heterotrophic bacteria. In contrast, production of extracellular superoxide is widespread throughout the fungal kingdom (22), where it is involved in host defense, posttranslational modification of proteins, hyphal branching, cell signaling, and cell differentiation (22,23).…”
mentioning
confidence: 99%
“…S1), the mechanism(s) controlling iron bioavailability to oceanic biota remain poorly understood. Iron bioavailability is influenced by photochemistry (3), chemical speciation (4,5), biological cycling (6), and uptake strategies (7)(8)(9). As a result, different microorganisms, each with its own specific iron requirement, iron uptake system(s), and biological adaptability (7,10,11), will have access to different pools of bioavailable iron under conditions of identical iron chemistry.…”
mentioning
confidence: 99%